THE EFFECTS OF OMEGA-3 INTAKE ON DELAYED ONSET MUSCLE SORNESS IN NON-ATHLET MEN - Ali Rajabi; Navid Lotfi; Arash Abdolmaleki; Shafieh Rashid-Amiri (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Delayed onset muscle soreness (DOMS) is classified as a muscle strain that presents with tenderness and stiffness one to two days after exercise. At present there are multiple proposed methods for treating DOMS, including anti-inflammatory medication, stretching, homeopathy, L-carnitine, rest and light exercise. The purpose of this study was to investigation of the effects of omega-3 intake on delayed onset muscle soreness in non-athlete men. 20 healthy subjects (age: 20.5±1.8 years) participated as subjects in this study. Subjects were randomly divided into two groups (experimental and control). In the experimental group, subjects consume daily 2000 mg of omega-3; 2 times per day for 1 month before and 48 hours after perform leg press exercise with eccentric pattern. Similarly, the was taking in the control group. The results showed significant decrease in severity of DOMS (CK and LDH levels and decreased knee's range of motion) in experimental group in comparison with control group (p<0.05). As a result of our study it is suggested that the use of omega-3 supplement can effectively reduce DOMS caused by eccentric exercise.